Imiona pochodzące od nazw geograficznych - Breza, Edward (Poznańskie Spotkania Językoznawcze, 2014)
The author focuses on names, which are derived from geographical names: names of countries, towns, villages, mountains, rivers. The analyzed names are based on the names listed in The Dictionary of Names Contemporary Used in Poland, published by Kazimierz Rymut (Kraków 1995), prepared on the basis of personal identity numbers of Polish citizens in 1994. The author distinguishes names derived from the names of countries, states, regions: Andaluzja, Angola, Arizona, Dziamajka, Elwetia, Germania, India, Kenia, Lechistan, Romania, Salwador, Syria; towns: Awila, Bazylea, Emaus, Hiroszima, Kremona, Lec, Lourdes, Medina, Moskwa, Naim, Orneta, Radomia, Rawenna, Reda, Santiago, Sewila, Sidney, Sienna, Szubin, Thorn, Tirana, Vienna, Warna, Wenecja/Venezia, Werona, Wienna, Winona, Winston, Wizna; mountains: Athos, Becerly, Morena; valleys: Sharon; peninsulas and islands: Floryda/Florida, Madera, Malta, Montserrat; rivers: Newa, Nida, Samara, Wisła; villages: Lubiana, Lubin; waterfall: Niagara; ambiguous: Roma.